Bayah Natural Zeolites to Upgrade the Quality of Bio Crude Oil from Empty Fruit Bunch Pyrolysis - Anton Irawan; Yazid Bindar; Teguh Kurniawan; Hafid Alwan; Rosid Rosid; Nisa Aina Fauziah (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Currently, the fuel oil for transportation and industry is produced mostly from fossil fuels. Because fossil fuels are a limited resource, biomass could be an alternative resource. Empty fruit bunch (EFB) is biomass waste from fresh fruit bunch processing in palm oil mills. EFB can be converted to bio-crude oil through pyrolysis at temperatures from 400 to 600 °C. The quality of bio-crude oil must be upgraded due to its high oxygen content. Esterification of bio-crude oil potentially improves the quality of bio-crude oil by using zeolite as catalyst. The purpose of this research was to investigate the properties of Bayah natural zeolites for upgrading the quality of bio-crude oil from EFB pyrolysis. Bayah natural zeolite was activated using various NaOH concentrations. Characterization of the natural zeolites was performed by using X-ray diffraction (XRD), scanning electron microscope-energy dispersive X-ray (SEM-EDX), and nitrogen physisorption. The optimum ratio of Si/Al of the modified Bayah natural zeolites was 3.91. The surface area of the parent was initially 19 m2/g and increased significantly to 150 m2/g after treatment with 0.4 M NaOH solution. The application of the activated zeolites for bio-crude oil esterification successfully decreased the total acid number.